PENGELOLAAN SISTEM KEUANGAN DAERAH DENGAN ACTUAL USAGE DENGAN PELATIHAN OPERATOR SISTEM INFORMASI PADA PEMERINTAH PROPINSI BANGKA BELITUNG - Marheni Marheni; Imam Alfikri Pratama (Budgeting: Jurnal Akuntansi Syariah, 2022)
This study aims to examine and analyze the significant effect of personal information system technical skills, system user training on the adoption of actual usage services and SIMDA performance in the Bangka Belitung provincial government. This research was an explanatory research The population taken in this study were SIMDA operators (OPD Regional Apparatus Organizations) in the Bangka Belitung Provincial Government as many as 62 people. Data analysis technique using path analysis Based on the results of the study, it can be concluded that: 1) The ability of personal information system techniques has a significant effect on SIMDA performance. The better the personal technical ability, the better SIMDA's performance; 2) System user training has no effect on SIMDA performance. Less than optimal training does not improve SIMDA performance; 3) Personal information system technical capabilities for the Adoption of SIMDA Actual Usage services; 4) Increasing operator capabilities will increase the adoption of SIMDA Actual Usage services; 5) System user training has no effect on SIMDA performance. Less than optimal training does not increase the adoption of SIMDA Actual Usage services and 6) Adoption of SIMDA Actual Usage services has a significant effect on SIMDA performance. The better the adoption of the Actual Usage service, the better SIMDA performance.